1997
DOI: 10.1021/jp962060q
|View full text |Cite
|
Sign up to set email alerts
|

Role of Platinum Deposits on Titanium(IV) Oxide Particles:  Structural and Kinetic Analyses of Photocatalytic Reaction in Aqueous Alcohol and Amino Acid Solutions

Abstract: Photocatalytic reaction at 298 K by platinum-loaded titanium(IV) oxide (TiO 2 -Pt) particles suspended in deaerated aqueous solutions of 2-propanol or (S)-lysine (Lys) was investigated. The TiO 2 catalysts with various amounts of Pt loadings were prepared by impregnation from aqueous chloroplatinic acid solution onto a commercial TiO 2 (Degussa P-25) followed by hydrogen reduction at 753 K. The physical properties of deposited Pt, e.g., particle size, surface area, and electronic state, were studied respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
172
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 259 publications
(196 citation statements)
references
References 62 publications
(119 reference statements)
15
172
0
Order By: Relevance
“…The presence of platinum as a co-catalyst is a necessary condition for H 2 evolution. In the H 2 system, methanol plays the role of a hole scavenger [10,51]. Time courses of CO 2 /H 2 gas evolution were linear as shown in Figure S7, supplementary data.…”
Section: Photocatalytic Activitymentioning
confidence: 88%
See 1 more Smart Citation
“…The presence of platinum as a co-catalyst is a necessary condition for H 2 evolution. In the H 2 system, methanol plays the role of a hole scavenger [10,51]. Time courses of CO 2 /H 2 gas evolution were linear as shown in Figure S7, supplementary data.…”
Section: Photocatalytic Activitymentioning
confidence: 88%
“…Many studies have been performed to obtain visible light activity by modification of titania with metal and non-metal elements [4][5][6][7]. The second limitation can be overcome by surface modification of titania with noble metals and their compounds that inhibit the charge recombination by increasing the transfer of photoexcited electrons from titania to substrates [5,[8][9][10]. Another approach is the preparation of p-n junction photocatalysts (e.g., nickel oxide/titania) to induce an internal electric field in the contact between p-type and n-type materials, which can increase e --h + separation [11].…”
Section: Introductionmentioning
confidence: 99%
“…In a series of studies on TiO 2 photocatalytic reactions, [48][49][50][51][52][53] we have shown that the overall kinetics depends on both the rates of reduction and oxidation by a photoexcited electron (e -) or positive hole (h + ), respectively, and the rate of recombination of e -and h + . To obtain a highly active TiO 2 photocatalyst, therefore, it is necessary to synthesize a TiO 2 powder that has contradictory properties, that is, large surface area to adsorb substrates and high crystallinity (or lesser surface and bulk defects) to diminish the e --h + recombination.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 6, with increasing KHP concentration, i net for TT, FT and FF decreased, probably due to poisoning of the TiO 2 photocatalyst by the high KHP concentration [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. An i net decrease for TF was not observed, and i net further increased with increasing KHP concentration.…”
Section: Photoelectrochemical Oxidation Of Organic Compoundsmentioning
confidence: 99%
“…anatase/rutile) may possess higher activity in *Corresponding author (email: s.zhang@griffith.edu.au) the photoelectrocatalytic degradation of organic compounds than pure anatase electrodes because the electron-transfer pathway from anatase phase to rutile phase facilitates the separation of photoelectron and photohole, extending the lifetime of the photoelectron and photohole [14]. Other TiO 2 modifications such as Pt 15 and Ag 16 doping have also been shown to improve organic degradation efficiency in photoelectrocatalytic processes, perhaps due to the Pt or Ag nanoparticles acting as electron traps and preventing exciton recombination.…”
mentioning
confidence: 99%